Media(ted) climate change in South Africa, Nigeria, and Kenya : reimagining the public for engagement - Okoliko, Dominic Ayegba (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.